KONFLIK BAGI HASIL TANGKAPAN PURSE SEINE DI PRIGI, TRENGGALEK, JAWA TIMUR - Wahyono, Ary (Jurnal Masyarakat dan Budaya, 2003)
The dependency relation has been occured between The boat owner (juragan darat) and crewmen (pandega) in small scale fishery, although this relation is not balance. Inbalancing relation is caused that the ordinary crewmen has owed to the boat owner. Their lives are supported by the boat owner. The boat owner supplies the basic needs to their families along they don’t go fishing. This phenomena is commonly happened in fishing community. This article will show there is no dependency of debt and conflict for sharing of catch in fishing community in Prigi, Jawa Timur.